Consumer Health Information Needs, Seeking and Searching Behavior By Rural Residents in the Kachia Grazing Reserve, with a Focus on Vector-borne Diseases - (:unkn) unknown (My University, 2019)
Information is considered the basic material for making decisions. People from all walks of life have information needs for business and personal use. Consumer Health Information (CHI) is an emerging form of information made accessible to the layperson. It is a simplified form of information from the types of information available to medical professionals. This study examines the health information behavior of the residents of one region in the Kachia Grazing Reserve (KGR) located in the North West of the six geopolitical zones of Nigeria. This dissertation explores the health information needs, seeking and searching behavior of the residents of selected communities that are affected by two vector-borne fly diseases in Nigeria. Insects such as flies are responsible for the transmission of diseases to humans, including trypanosomiasis, caused by the tsetse fly, and malaria, caused by mosquitos. These flies are commonly found in and affect mostly rural dwellers in Nigeria. This study investigates some of the broader contextual issues that may influence consumer health care needs as well as seeking-searching behavior. It asks participants whether they believe their health information needs are being met or not. The study applied a qualitative approach to sampling 50 adult participants. It relied on a triangulation data collection method using a questionnaire, interview instrument, and focus group discussion. NVivo version 12 was used in the data analysis to create a coding scheme following the stages of open, axial, and selective coding processes to develop a grounded theory of rural residents’ information behaviors. The findings of the research revealed various health information needs and seeking behavior the rural residents engaged in; it also revealed the factors that influenced their seeking and searching activities. Furthermore, the findings highlighted the information sources they used and the problems associated with the information-seeking and searching process. The model that was inductively derived from the grounded theory data analysis explains further in detail the strategies and processes members of the community use in their health information-seeking and health-searching behavior.
Keywords: Consumer Health; Disease and Sickness; Information Need; Information Seeking & Serching Behavior; Rural Communities; Tsetse fly and Mosquito